STUDY OF GLASSY STATES OF CRYOCONDENSATES OF ORGANIC MOLECULES - Suiinzhanova, U.P.; Aldiyarov, A.U.; Beisenov, K.L. (Recent Contributions to Physics, 2022)
Cryovacuum gas condensates, especially those prone to the formation of glassy states with their subsequent transformations, are ideal objects for studying the processes occurring in disordered amorphous solid-state systems. The fact that it is possible to precisely control the conditions of cryo-deposition, such as the condensation temperature and the rate of cryo-film formation, makes it possible to establish an unambiguous correlation between the properties of cryo-condensates and the specified conditions for their formation. Ultrastable glasses (predominantly from the vapor phase under optimal deposition conditions) are a unique class of materials with low enthalpies and high kinetic stability. These highly stable and dense glasses have unique physicochemical properties, such as high thermal stability, improved mechanical properties, or anomalous supercooled transitions. At T=70 K, the transition from the amorphous glassy state (GS) to the liquid-solid cooled phase (SCL) occurs, after which its crystallization in the temperature range of 75-78 K passes into the plastic crystalline state (PC)-a cubic volume-centered structure with a directionally unregulated rotating subsystem. At T = 78-80 K, the transformation of the plastic crystal into a monoclinic crystal (MC) begins, which ends at T = 83 K.